2014
DOI: 10.1111/obr.12208
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pre‐school‐ and school‐based interventions to impact weight‐related behaviours in African American children and youth: a literature review

Abstract: SummaryThis review assessed the effectiveness of pre-school-and school-based obesity prevention and/or treatment interventions targeting healthy eating, physical activity or obesity in African American children and adolescents. Systematic searches were conducted for English-printed research articles published between January 1980 and March 2013. Retained articles included experimental studies conducted in the United States that targeted ≥80% African American/black children and adolescents and/or studies whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 60 publications
1
36
0
2
Order By: Relevance
“…These results supported the findings of several systematic reviews of school-based nutrition interventions, which report moderate evidence of BMI reduction (24,25). One of these reviews, Lavelle et al (33) found that interventions that targeted overweight/obese children reduced their BMI by 0.35 (95% CI: 0.12, 0.58, P = 0.003).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results supported the findings of several systematic reviews of school-based nutrition interventions, which report moderate evidence of BMI reduction (24,25). One of these reviews, Lavelle et al (33) found that interventions that targeted overweight/obese children reduced their BMI by 0.35 (95% CI: 0.12, 0.58, P = 0.003).…”
Section: Discussionsupporting
confidence: 72%
“…However, less than 1% of the child nutrition program directors in Mississippi are registered dietitians, a statistic that is similar in many states. Schoolbased nutrition interventions have shown positive effects on body mass index (BMI) values in elementary children, but mixed results have been reported (20)(21)(22)(23), and few interventions have been conducted with African American children (24). Also, as stated by Roseman et al (25) who recommended multi-component interventions, the opportunities for extended impact in school-based interventions may be limited when faced with the challenges of the school schedule, academic testing, state-mandated curricula, and multiple levels of school administration.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, a wealth of research has been conducted in an attempt to alleviate the disturbing trends in these health domains. However, research indicates that these interventions have had limited success [1][2][3][4]. Largely unexplored is the understanding of how the development of multiple health-related variables may synergistically impact each other to promote either positive or negative trajectories of health.…”
Section: Introductionmentioning
confidence: 99%
“…School-based nutrition interventions have shown positive effects on body mass index (BMI) values in elementary children, but with mixed results (17)(18)(19)(20), and few interventions have been conducted with African American children (21). This lack of information can make it hard to design interventions for areas with a high percentage of African-Americans, like in Mississippi and the Mississippi Delta.…”
Section: Introductionmentioning
confidence: 99%
“…In a literature review of all pre-school and school-based obesity prevention or treatment interventions, Robinson et al (21) found only 17 studies published between January 1980 and March 2013 that targeted populations that were more than 80% African American. The authors stressed that there are still deficits in understanding what must be done to address the disparities that contribute to obesity in this population (21).…”
Section: Introductionmentioning
confidence: 99%